Studying subcellular detail in fixed astrocytes: dissociation of morphologically intact glial cells (DIMIGs) - Haseleu, Julia; Anlauf, Enrico; Blaess, Sandra; Endl, Elmar; Derouiche, Amin (Frontiers in Cellular Neuroscience, 2013)
Studying the distribution of astrocytic antigens is particularly hard when they are localized in their fine, peripheral astrocyte processes (PAPs), since these processes often have a diameter comparable to vesicles and small organelles. The most appropriate technique is immunoelectron microscopy, which is, however, a time-consuming procedure. Even in high resolution light microscopy, antigen localization is difficult to detect due to the small dimensions of these processes, and overlay from antigen in surrounding non-glial cells. Yet, PAPs frequently display antigens related to motility and glia-synaptic interaction. Here, we describe the dissociation of morphologically intact glial cells (DIMIGs), permitting unambiguous antigen localization using epifluorescence microscopy. Astrocytes are dissociated from juvenile (p13–15) mouse cortex by applying papain treatment and cytospin centrifugation to attach the cells to a slide. The cells and their complete processes including the PAPs is thus projected in 2D. The entire procedure takes 2.5–3 h. We show by morphometry that the diameter of DIMIGs, including the PAPs is similar to that of astrocytes in situ. In contrast to cell culture, results derived from this procedure allow for direct conclusions relating to (1) the presence of an antigen in cortical astrocytes, (2) subcellular antigen distribution, in particular when localized in the PAPs. The detailed resolution is shown in an exemplary study of the organization of the astrocytic cytoskeleton components actin, ezrin, tubulin, and GFAP. The distribution of connexin 43 in relation to a single astrocyte's process tree is also investigated.